THE RIGHTS OF UZBEK AND BRITISH WOMEN IN THE 20TH CENTURY AND THEIR ROLE TODAY - Numonova Ozoda; Khujamurodova Fayoza (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The 20th century was a transformative period for women’s rights, both in Uzbekistan and the United Kingdom. As both societies experienced significant social, political, and economic changes, the role of women evolved dramatically. This article explores the historical context of women’s rights in these two countries and examines their contemporary roles and contributions.